2005
DOI: 10.1002/ptr.1607
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant potential of the cultured mycobiont of a lichen Usnea ghattensis

Abstract: The biologically active compounds, antioxidant activities and free radical scavenging effects of dry matter of cultural medium (DMCM), filtrate (DMF) and different solvent extracts of mycobiont from lichen species Usnea ghattensis in submerged culture (UGSC) were investigated. DMF showed the strongest inhibition of lipid peroxidation as a function of its concentration, and was comparable to the antioxidant activity of BHA at the same concentration of 0.2 mg/mL. The hexane extract of mycobiont had the weakest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…The recent studies indicated that antioxidant activity of glycoproteins was associated with glycosidic linkage, the content of protein and carbohydrate, molecular weight, compositions of amino acid and monosaccharide, etc. (Fuad, 2006;Behera et al, 2005;Liu and Zhao, 2011;Heo and Lim, 2004;Lo et al, 2011;Dahl and Richardson, 1978). Fuad (2006) reported that the O-glycosidic linkage was not important for in vitro bioactivity, but it played an important role in vivo bioactivity.…”
Section: Discussion About the Possible Antioxidant Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent studies indicated that antioxidant activity of glycoproteins was associated with glycosidic linkage, the content of protein and carbohydrate, molecular weight, compositions of amino acid and monosaccharide, etc. (Fuad, 2006;Behera et al, 2005;Liu and Zhao, 2011;Heo and Lim, 2004;Lo et al, 2011;Dahl and Richardson, 1978). Fuad (2006) reported that the O-glycosidic linkage was not important for in vitro bioactivity, but it played an important role in vivo bioactivity.…”
Section: Discussion About the Possible Antioxidant Mechanismmentioning
confidence: 99%
“…However, N-glycosidic linkage was opposite to O-glycosidic linkage. It has been reported that the superoxide radical scavenging activity of polysaccharide extracts appears to depend on the amount of protein or peptide present in the form of polysaccharide-protein or polysaccharide-peptide complexes, lower polysaccharide/protein or polysaccharide/ peptide ratios can exhibit the excellent scavenging ability (Behera et al, 2005). Our results indicated that the increase of protein and carbohydrate contents of glycoproteins through consecutive separation and purification can lead to the improvement of DPPH radical scavenging activity, which is in good agreement with other reports in the literature Liu and Zhao, 2011).…”
Section: Discussion About the Possible Antioxidant Mechanismmentioning
confidence: 99%
“…[32] Polysaccharopeptide obtained from mushrooms have lower polysaccharide/peptide ratios and exhibits the strongest scavenging effects. [33,34] It was found that EPSP from G. lucidum were complexes of polysaccharides (71.88%) and proteins (28.12%). [35] Perhaps this was why EPSP from G. lucidum had more powerful free radical scavenging capacity and reducing power.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant activity of lichens are evidenced by the presence of phenols 17 . A decrease in absorbance of the reaction mixture indicated a higher free radical scavenging activity.…”
Section: Antioxidant Activitymentioning
confidence: 99%